Metode Guru Sekolah Minggu dalam Pengajaran Doa-Doa Pokok terhadap Anak Minggu Gembira di Stasi ST. Yohanes Don Bosco Sukajulu Tiga Jumpa - Pelta Ginting; Widya Anzelica Br Tarigan (Penerbit Goodwood, 2023)
Purpose: This research aims to explore the methods used by Sunday School teachers to teach fundamental prayers to the children of Minggu Gembira at St. Yohanes Don Bosco Sukajulu Tiga Jupa. Methodology: This study adopted a qualitative approach using a single case study method. Data were collected through observation, interviews, and documentation. The findings reveal that the teaching methods employed by Sunday schoolteachers include the use of visual media, repetition, and real-life examples. Results: This study explored the effectiveness of The Sunday School teacher's method in teaching the main prayers to the children of Sunday Joy at St. John Don Bosco Sukajulu Tiga Jumpa Station. Results indicate that this method shows promise in enhancing children's understanding and retention of key prayers Limitations: The limitations include small sample size and limited generalizability to other settings. Further research is required to assess the long-term impact of this method on children's spiritual growth and development. Contribution: This study contributes to the development of teaching methods for fundamental prayers in Sunday Schools and provides insights into how Minggu Gembira children respond to teaching methods.